2001
DOI: 10.1053/euhj.2000.2533
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of heart failure in the general population. The Rotterdam Study

Abstract: Heart failure generally afflicts older subjects in the community, carries a poor prognosis, especially in the presence of concomitant diseases, and confers a fivefold increase in the risk of sudden death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
220
9
18

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(262 citation statements)
references
References 41 publications
13
220
9
18
Order By: Relevance
“…Two studies have found that high adiponectin levels are associated with increased mortality in heart failure patients [18,19], perhaps because high levels of adiponectin are indicative of systemic wasting in this population [6]. In this regard, low body mass index, which leads to elevated adiponectin levels, is associated with increased mortality following the onset of heart failure, whereas elevated body mass index, which leads to reduced adiponectin levels, increases the risk for developing heart failure [29,30]. Similarly, hypercholesterolemia is predictive of improved survival in heart failure patients presumably because it is a surrogate marker of body mass [31].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have found that high adiponectin levels are associated with increased mortality in heart failure patients [18,19], perhaps because high levels of adiponectin are indicative of systemic wasting in this population [6]. In this regard, low body mass index, which leads to elevated adiponectin levels, is associated with increased mortality following the onset of heart failure, whereas elevated body mass index, which leads to reduced adiponectin levels, increases the risk for developing heart failure [29,30]. Similarly, hypercholesterolemia is predictive of improved survival in heart failure patients presumably because it is a surrogate marker of body mass [31].…”
Section: Discussionmentioning
confidence: 99%
“…HF is a complex clinical syndrome and it is the final and most severe manifestation of nearly every form of heart disease (4,5). The prognosis of HF is particularly poor, with fewer than 50% of subjects remaining alive by 5 years, and only 10% by 10 years following the initial diagnosis (14)(15)(16)(17). Likewise, we recently found that HF is an important contributor to the excess overall mortality in RA (Crow- …”
Section: Discussionmentioning
confidence: 99%
“…The probability of death for patients with stable CAD or patients in the different postevent health states was estimated by multiplying the age‐adjusted probability of death not attributed to an MI or stroke in the general population by a disease‐specific mortality multiplier (Table 1). 18, 19, 20, 21 …”
Section: Methodsmentioning
confidence: 99%